Asymmetric total synthesis of a putative sex pheromone component from the parasitoid wasp Trichogramma turkestanica - Geerdink, Danny; Buter, Jeffrey; van Beek, Teris A.; Minnaard, Adriaan J. (Beilstein Journal of Organic Chemistry, 2014)
Virgin females of the parasitoid wasp Trichogramma turkestanica produce minute amounts of a sex pheromone, the identity of which has not been fully established. The enantioselective synthesis of a putative component of this pheromone, (6S,8S,10S)-4,6,8,10-tetramethyltrideca-2E,4E-dien-1-ol (2), is reported as a contribution to this identification. Catalytic asymmetric conjugate addition of methylmagnesium bromide and stereoselective Horner–Wadsworth–Emmons olefinations are used as the key steps, and 2 was obtained in 16 steps with an overall yield of 4.4%.
Keywords: asymmetric catalysis; copper; deoxypropionates; natural products; sex pheromone; Trichogramma turkestanica